Sertoli-cell-specific knockout of connexin 43 leads to multiple alterations in testicular gene expression in prepubertal mice - Sarah Giese; Hamid Hossain; Melanie Markmann; Trinad Chakraborty; Svetlin Tchatalbachev; Florian Guillou; Martin Bergmann; Klaus Failing; Karola Weider; Ralph Brehm (The Company of Biologists, 2012)
SUMMARY A significant decline in human male reproductive function has been reported for the past 20 years but the molecular mechanisms remain poorly understood. However, recent studies showed that the gap junction protein connexin-43 (CX43; also known as GJA1) might be involved. CX43 is the predominant testicular connexin (CX) in most species, including in humans. Alterations of its expression are associated with different forms of spermatogenic disorders and infertility. Men with impaired spermatogenesis often exhibit a reduction or loss of CX43 expression in germ cells (GCs) and Sertoli cells (SCs). Adult male transgenic mice with a conditional knockout (KO) of the Gja1 gene [referred to here as connexin-43 (Cx43)] in SCs (SCCx43KO) show a comparable testicular phenotype to humans and are infertile. To detect possible signaling pathways and molecular mechanisms leading to the testicular phenotype in adult SCCx43KO mice and to their failure to initiate spermatogenesis, the testicular gene expression of 8-day-old SCCx43KO and wild-type (WT) mice was compared. Microarray analysis revealed that 658 genes were significantly regulated in testes of SCCx43KO mice. Of these genes, 135 were upregulated, whereas 523 genes were downregulated. For selected genes the results of the microarray analysis were confirmed using quantitative real-time PCR and immunostaining. The majority of the downregulated genes are GC-specific and are essential for mitotic and meiotic progression of spermatogenesis, including Stra8, Dazl and members of the DM (dsx and map-3) gene family. Other altered genes can be associated with transcription, metabolism, cell migration and cytoskeleton organization. Our data show that deletion of Cx43 in SCs leads to multiple alterations of gene expression in prepubertal mice and primarily affects GCs. The candidate genes could represent helpful markers for investigators exploring human testicular biopsies from patients showing corresponding spermatogenic deficiencies and for studying the molecular mechanisms of human male sterility.